Mountain waves over Himalayas (MAUSAM, 1989)
This paper documents the observational evidence of mountain waves over western and central Himalayas. The observed wavelength of the cases presented varies from 13 km. The most marked and well-organized mountain waves are observed to the lee of western and central Himalayas over Tibet plateau, which is also the region of highest frequency of wave occurrence. Mean stability profile associated with mountain waves has been developed and it shows high stability in the layer 5-9 km with less stability aloft.